Drosophila BRUCE inhibits apoptosis through non-lysine ubiquitination of the IAP-antagonist REAPER - Domingues, C (Nature Publishing Group, 2012)
Active caspases execute apoptosis to eliminate superfluous or harmful cells in animals. In Drosophila, living cells prevent uncontrolled caspase activation through an inhibitor of apoptosis protein (IAP) family member, dIAP1, and apoptosis is preceded by the expression of IAP-antagonists, such as Reaper, Hid and Grim. Strong genetic modifiers of this pathway include another IAP family gene encoding an E2 ubiquitin conjugating enzyme domain, dBruce. Although the genetic effects of dBruce mutants are well documented, molecular targets of its encoded protein have remained elusive. Here, we report that dBruce targets Reaper for ubiquitination through an unconventional mechanism. Specifically, we show that dBruce physically interacts with Reaper, dependent upon Reaper's IAP-binding (IBM) and GH3 motifs. Consistently, Reaper levels were elevated in a dBruce −/− background. Unexpectedly, we found that dBruce also affects the levels of a mutant form of Reaper without any internal lysine residues, which normally serve as conventional ubiquitin acceptor sites. Furthermore, we were able to biochemically detect ubiquitin conjugation on lysine-deficient Reaper proteins, and knockdown of dBruce significantly reduced the extent of this ubiquitination. Our results indicate that dBruce inhibits apoptosis by promoting IAP-antagonist ubiquitination on unconventional acceptor sites.